IMPLEMENTASI KEBIJAKAN PENANGGULANGAN STUNTING DI DESA SIMPUNG LAYUNG KECAMATAN MUARA UYA KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Stunting or short stature is a growth disorder that is mostly caused by nutritional problems. The role of parents is very important to prevent these problems. Stunting according to WHO is a developmental disorder experienced by children due to malnutrition, repeated infections, and inadequate psychosocial stimulation. Children are defined as stunted if their height for age is more than two standard deviations below the WHO child growth standard median. Stunting in early life is especially noticed in the first 1,000 days to two years of age. Growth retardation has a detrimental functional impact on the child. The purpose of this study was to find out and analyze the extent to which the understanding and success of Stunting Management Policy Implementation was seen from the Communication Aspect in Simpung Layung Village, Muara Uya District, Tabalong Regency from Communication Indicators, Human Resources, Disposition, and Bureaucratic Structure. This research method uses descriptive qualitative research methods. Techniques for collecting data through the process of observation, interviews and data analysis according to Miles, Huberman and Saldana (2014) are interactive analysis models 1. Data condensation stage, 2. Data display/data presentation, 3. Conclusion: Drawing/verifying (drawing conclusions) . Based on the research results obtained by researchers at the research location, the Implementation of Stunting Management Policy in View of the Communication Aspect in Simpung Layung Village, Muara Uya Sub-District, Tabalong Regency was implemented. Keywords: Implementation, Policy, Stunting Prevention